Modalities of sequential human robot collaboration trigger different modifications of trunk oscillations - Ranaldi, Simone; Bibbo, Daniele; Corvini, Giovanni; Schmid, Maurizio; Conforto, Silvia (Frontiers in Neurorobotics, 2023)
Human robot collaboration is quickly gaining importance in the robotics and ergonomics fields, due to its ability to reduce biomechanical risk on the human operator while increasing task efficiency. The performance of the collaboration is typically managed by the introduction of complex algorithms in the robot control schemes to ensure optimality of its behaviour; however, a set of tools for characterizing the response of the human operator to the movement of the robot has yet to be developed. In this paper, trunk acceleration was measured and used to define descriptive metrics during various human robot collaboration strategies. The results show that such a description can be easily developed using methods from recurrence quantification analysis; moreover, the parameter values highlight that, when designing strategies for human robot collaboration, ensuring that the subject maintains control of the rhythm of the task is a critical factor, as it enables to maximize comfort in task execution, without affecting efficiency.